Baclofen-Responsive Hiccups After Esophageal Stenting for Malignancy-Related Dysphagia. Issue 2 (1st April 2016) - Sharma, Vishal; De, Arka; Lamoria, Sandeep; Lamba, Brinder Mohan Singh
Abstract : Hiccups can have multiple causes, including esophageal lesions. Hiccups after insertion of self-expanding metallic stents have been reported occasionally following stenting for lesions of the gastroesophageal junction. We report a patient who developed hiccups after insertion of a stent for squamous cell carcinoma of the proximal esophagus. The hiccups responded only to the initiation of baclofen therapy.